(untitled) (Asian Journal of Social Science Studies, 2022)
In Article 2 of the latest revision of the Anti-Unfair Competition Law, the definition of unfair competition includes "harming consumers’ interests". In the Internet context, the position of consideration of consumers’ interests is more complex, and there are often different conclusions from different perspectives. For example, some conducts that seem to be beneficial to consumers in the short run, will ultimately harm consumers’ interests in the long run. The consideration of consumers’ interests should be based on an independent status and a dynamic approach.